2002
DOI: 10.1177/0013164402238088
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Structure, and Correlates of Learning and Study Strategies Inventory Scores

Abstract: The Learning and Study Strategies Inventory (LASSI) is used in hundreds of universities and high schools each year. This study investigated the reliability, structure, and criterion-related validity of LASSI scores. Data were provided by 502 university students. Results suggest that the LASSI may not measure the postulated 10 scales typically used to report results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 13 publications
1
23
0
2
Order By: Relevance
“…Previous proposed constructs to explain low academic performance include study skills (e.g., Aaron, 1999), study habits (e.g., Murray, 2003), study attitudes (e.g., Zimmerman, 1977), study motivation (e.g., Melancon, 2002), meta-cognitive skills (e.g., Zeegers, 2001), study anxiety (e.g., Miller, 1972), procrastination (e.g. Pychyl, 2000) and depth of processing (e.g., Hall, 2001).…”
Section: Chronology Of the Study Of Study Habitsmentioning
confidence: 99%
“…Previous proposed constructs to explain low academic performance include study skills (e.g., Aaron, 1999), study habits (e.g., Murray, 2003), study attitudes (e.g., Zimmerman, 1977), study motivation (e.g., Melancon, 2002), meta-cognitive skills (e.g., Zeegers, 2001), study anxiety (e.g., Miller, 1972), procrastination (e.g. Pychyl, 2000) and depth of processing (e.g., Hall, 2001).…”
Section: Chronology Of the Study Of Study Habitsmentioning
confidence: 99%
“…In the years following the publication of the first and second versions of the LASSI, the Inventory has been the subject of a number of significant independent statistical analyses. These studies have confirmed the Inventory's reliability and validity, examined its use in cross-cultural settings, and investigated correlations between scores on the Inventory and age, gender and student success (Cano, 2006;Prevatt, Petscher, Proctor, Hurst & Adams, 2006;Flowers, 2003;Bender & Garner, 2010;Ning & Downing, 2010;Melancon, 2002;Yip & Chung, 2005;Ola, Morakinyo & Adewuya, 2009;Olaussen & Braten, 1998;Braten & Olaussen, 1998;Marrs, Sigler & Hayes, 2009;Carson, 2011;Flowers, Bridges & Moore, 2011). Those studies that have used the LASSI outside the American context have demonstrated that the instrument generally retains its value in cross-cultural environments (Olaussen & Braten, 1998).…”
Section: The Lassimentioning
confidence: 99%
“…This measure has been translated into over 30 languages and is estimated to be in use by half of all colleges in the United States (Murray, 1998). There have been numerous empirical evaluations using the LASSI (e.g., Melancon, 2002;Murphy & Alexander, 1998;Olaussen & Braten, 1998;Olejnik & Nist, 1992;Olivarez & Tallent-Runnels, 1994;Samuelstuen, 2003;Yip & Chung, 2002). However, there have been few studies of any sort (LASSI or otherwise) on the ADHD college population.…”
Section: Significance Of the Studymentioning
confidence: 99%